Formulating psychosis: a thematic analysis of CBTp trainees’ experiences - Newman-Taylor, K; Wood, R; Ellis, A; Isham, L (Cambridge University Press, 2022)
The NICE guidance states that cognitive behavioural therapy (CBT) should now be offered to everyone with psychosis in the UK. This has rightly resulted in an increased demand for adherent therapy from qualified clinicians. Individualised formulation is a key component of CBT for psychosis, yet many trainees struggle to make sense of and apply the theoretical models on which these are based. This study explored trainee and recently qualified therapists’ experience of formulating CBT for psychosis, to help us understand how best to guide training and clinical practice. We ran focus groups with trainees who were completing, or had recently completed, postgraduate training in CBT for psychosis. We then analysed verbatim transcripts of the semi-structured interviews. and completed a thematic analysis of the data using inductive open coding. Three over-arching themes were generated: (1) purpose of formulation, (2) formulation in practice, and (3) (reflection on) learning to formulate. Training programmes and clinical supervisors should focus on fostering trainees’ and newly qualified therapists’ ability to develop simple, targeted formulations. These will draw on maintenance and developmental models of psychosis, depending on the person’s needs and goals. Opportunities for procedural learning are likely to improve skilful formulation, and use as the basis for therapeutic change.